On Orthogonal Partial b-Metric Spaces with an Application - Khalil Javed; Hassen Aydi; Fahim Uddin; Muhammad Arshad (Journal of Mathematics)
In this paper, we initiate the concept of orthogonal partial b-metric spaces. We ensure the existence of a unique fixed point for some orthogonal contractive type mappings. Some useful examples are given, and an application is also provided in support of the obtained results.